FENOMENA SELEB TIKTOK: GEN Z DAN PERSONAL BRANDING - Mona, Eflina Nurdini Febrita (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
This study examines how Generation Z TikTok celebrities in Malang, Indonesia, build sustainable personal branding strategies that align with the Sustainable Development Goals (SDGs) and the vision of Society 5.0. As social media becomes a dominant space for shaping digital identity and influence, personal branding takes on a new meaning—not just for self-promotion, but also for social impact. Using a descriptive qualitative method, this research involves in-depth interviews with six TikTok celebrities selected through purposive sampling. The study found that these celebrities develop their personal branding through consistent content creation, audience interaction, and a value-based narrative that emphasizes education, gender equality, environmental awareness, and community empowerment—aligning their digital persona with several SDGs, such as SDG 4 (Quality Education) and SDG 13 (Climate Action). The celebrities also demonstrated adaptability in navigating algorithmic trends while maintaining authenticity and long-term interaction. These findings highlight how Gen Z celebrities strategically align personal and social values through digital platforms, offering insights into sustainable branding within the context of Society 5.0. This research contributes to the understanding of how digital identity, youth culture, and global goals intersect in the evolving landscape of celebrity communication.   Keywords: Personal Branding, Tiktok, Social Media, Celebrity, Digital Marketing.